Reversing the Placebo: Performance‐Branded Experiences Can Undermine Consumer Performance - Banker, Sachin; Gosline, Renée Richardson; Lee, Jeffrey K. (Journal of Consumer Psychology, 2020)
Products bearing premium brand labels are known to increase perceptions of efficacy and improve objective consumer performance relative to lesser‐branded equivalents, in what is traditionally described as a marketing placebo effect. In this paper, we suggest that experiences bearing these highly regarded brand labels can lead to a reverse effect, such that consumer performance actually declines with their use. Our findings demonstrate across domains of improving mental acuity, learning a new language, and developing financial analysis skills that completing performance‐branded training experiences impairs objective performance in related tasks, relative to lower‐performance‐branded or unbranded counterparts. We posit that branded training experiences can evoke a brand‐as‐master relationship in which consumers take on a subservient role relative to the brand. As a consequence, higher‐performance brands may impose greater demands upon consumers, increasing performance‐anxiety and interfering with an individual's ability to perform effectively. These results document an important ramification of applying branding to learning experiences and identify contexts in which traditionally positive marketing actions can backfire for consumers.